Simple and stable elbow dislocations: results after conservative treatment - Calderazzi, Filippo (Acta Biomed, 2020)
BACKGROUND AND AIM OF THE WORK: In adults, elbow dislocations are second in frequency after shoulder dislocations. They are often the result of a trauma due to accidental falls on the palm of the hand with the elbow flexed. In most cases this mechanism produces a posterior dislocation of the radius and ulna with respect to the humerus. The therapeutic approach was usually conservative in the past and it was characterized by manual reduction and plaster immobilization. More recently, as consequence of biomechanic and pathophysiology studies, the management of these injuries has gradually changed. The current trend is to immobilize the elbow only for few days and to evaluate its stability several times. In case of instability surgery may be indicated. The aim of this study was to assess the outcomes of simple stable elbow dislocations treated conservatively between january 2012 and december 2018. METHODS: Twenty-six patients were included. All subjects underwent to a follow-up visit, in which clinical functional tests were performed in order to evaluate any stiffness in flexion-extension, prono-supination and instability in varus-valgus. In addition, patients were asked to complete three questionnaires (DASH, MEPS, SF-36) to evaluate how much the pathology interfered with ADL’s. RESULTS: Outcomes showed that prolonged immobilization increased stiffness in flexion and extension with the need of longer reabilithation. The recovery of prono-supination was instead always optimal. ADL’s migth be influenced by the traumatic event and its management. CONCLUSIONS: Results of conservative treatment of simple elbow dislocation are generally satisfactory. A precise flow-chart of the patient management after trauma is essential in order to detect unstable lesions and to plan the correct therapy. This is the basis for the prevention of joint stiffness and long-term insatbility.